Do agriculture interventions increase aspirations? An examination from the lens of caste and gender - Alvi, Muzna; Ward, Patrick S.; Spielman, David J.; Makhija, Simrin (Agricultural and Applied Economics Association, 2019)
We use priming, a concept popular in social psychology, to study the effect of identity salience on aspirations for one’ self and children as part of an impact evaluation in Odisha, India. We measure the effect of an individual’s gender- and caste-identity salience on improving aspirations for their children’s profession and education. We find that when women are primed on gender, they exhibit higher aspirations for their daughters. Similarly, low-caste women primed on caste are more aspirational for their daughters. We do not find similar results for men. The effect of caste priming is more apparent in areas where significant heterogeneity exists and muted in homogenous areas. We find that aspirations for boys are already very high, thus priming has no effect on aspirations for sons.